Construction of binary phase diagram of palm kernel oil based glucosides - Osman, Faizza Nur Atika (2017)
The purpose of this study is to prepare a series of glucosides sample in water with different concentrations and to construct the binary phase diagram from palm kernel oil based glucosides. Glucosides with an average alkyl chain length of 14 carbon atoms derived from fatty acid of palm kernel oil have been synthesized and their phase behavior has been studied. The phase diagram is a best way to show formation of different phases with a given temperature and concentration. With construct a phase diagram can know how to use it to predict behavior of materials which is glucosides. These phase diagrams provides boundaries of different phases. The binary phase diagrams of glucosides are constructed using cross polarizer films and optical polarizing microscopy (OPM). A rich phase behavior with lamellar, normal hexagonal, and bicontinuous cubic regions, as well as water-rich solutions, was observed.